High-dose vitamin C as a targeted treatment for KRAS-driven cancers? - Elisabeth Mack; Christian Rau; Cornelia Otet; Jonas Aaron Schäfer; Cornelia Brendel; Albert Grass; Peer Bredow; Christian Hohl; Carsten Denkert; Frank Willeke; Andreas Neubauer (Redox Biology)
KRAS mutations are frequently observed in human cancer and are associated with proliferation, therapy-resistance and worse outcome. Regrettably, only a fraction of possible mutations is druggable. Therefore, a tailored and possibly cost-effective method to overcome this issue is urgently needed.Recently, Bodeker et al. presented a randomized phase II trial investigating whether high-dose vitamin C (ascorbate) improved overall survival in metastatic pancreatic cancer (Bodeker et al., Redox Biol 2024). This may be due to the high frequency of KRAS mutations in pancreatic cancer (>90 %), as, in the case of oncogenic RAS, high-dose vitamin C becomes synthetic lethal when added to chemotherapy, as previously shown by the work of Cantley and coworkers (Yun et al., Science, 2015)It is unclear, however, if this observation holds true also for rare KRAS mutations. Recently we treated a 43 year old male patient with metastatic duodenal cancer and an atypical KRAS mutation A59T using FOLFOX-chemotherapy with high-dose vitamin C as second line therapy. The tumor had progressed after first line immune checkpoint therapy as the tumor presented with microsatellite instability. Restaging after 8 cycles of FOLFOX + high-dose vitamin C therapy revealed regression of the tumor mass and extensive tumor necrosis. Thus, our personalized experimental approach yielded in a greater clinical benefit for the patient than the previous standard therapy, particularly a PFS-2/PFS-1 ratio of >2.Obviously we do not know whether this response could have also been observed if chemotherapy was given w/o high-dose vitamin C. As up to now two randomized clinical trials showed a beneficial effect of the addition of high-dose vitamin C (pancreatic cancer: Bodeker et al., colorectal cancer: Vitality trial), and, in the case of Vitality, the benefit was restricted to KRAS mutated tumors only, more clinical trials addressing this topic are needed. Therefore, we thank Bodeker et al. for contributing these important data.